Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1152/jappl.1985.59.3.784
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoconstriction in asthmatics exposed to sulfur dioxide during repeated exercise

Abstract: Young male volunteers with mild asthma and hypersensitivity to methacholine were exposed for 75 min with natural breathing to 0.0, 0.25, 0.5, and 1.0 ppm SO2. Each exposure included three 10-min periods of moderate treadmill exercise (minute ventilation 21 l . m-2 . min-1, O2 consumption 25 ml . kg-1, and heart rate 120/min). Specific airway resistance (sRaw) was not significantly increased after exercise in 0.25 ppm SO2, relative to the control exposure (clean air). In 0.5 and 1.0 ppm SO2, sRaw was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In a study carried out in Sweden it was observed that increased concentrations of PM10 and SO in the air resulted in a decrease in the percentages of FVC and FEV1, respectively (22). In a study by Goren et al in Israel, the annual increase in FVC and FEV1 was lowest in the four subgroups from the community expected to be the most polluted, but highest in the community expected to be moderately polluted, implying that not only FEV1 but also FVC is a!ected by the increase of pollutants in the air (16).…”
mentioning
confidence: 99%
“…In a study carried out in Sweden it was observed that increased concentrations of PM10 and SO in the air resulted in a decrease in the percentages of FVC and FEV1, respectively (22). In a study by Goren et al in Israel, the annual increase in FVC and FEV1 was lowest in the four subgroups from the community expected to be the most polluted, but highest in the community expected to be moderately polluted, implying that not only FEV1 but also FVC is a!ected by the increase of pollutants in the air (16).…”
mentioning
confidence: 99%
“…Two studies showing effects at lower concentrations were not considered relevant because of limitations in study design (Islam et al 1992(Islam et al , 1994; no normal breathing was tested). Asthmatic volunteers showed the same irritant-induced airway reactions as healthy individuals but showed these reactions at (slightly) lower levels (Linn et al 1984a, b;Schachter et al 1984;Sheppard et al 1984;Bethel et al 1985;Roger et al 1985;Witek and Schachter 1985;Kehrl et al 1987;Gong et al 2001). Their susceptibility may have been strongly influenced by the (forced) physical activity and atmospheric conditions such as breathing dry and/or cold air (Samet 1995;Venables and Chan-Yeung 1997), conditions during which ventilation is enhanced (Utell and Looney 1995).…”
Section: Sulphur Dioxidementioning
confidence: 99%
“…immediate Considered as immediately dangerous to life and health (HSDB 1998) 150 immediate Death (Huber and Loving 1991) !0.2 24 h Excess mortality may occur (Amdur et al 1991;Mazumdar et al et al 1982;WHO 1979) (Sheppard et al 1980) 0.4-1.0 3-10 min Significant increases in airway resistance (Bethel et al 1985;Linn et al 1983Linn et al , 1984Roger et al 1985;Schachter et al 1984) 0.25 3-10 min Significant changes in airway resistance in young adult mild asthmatics (Sheppard et al 1981) 0.1 10 min Slight increase in specific airway resistance of sensitive asthmatics (Sheppard et al 1981) !0.25 3 min Increase in specific airway resistance (Myers et al 1986a, b) 0.1-0.5 Lack of significant lung function changes in asthmatics (Jorres and Magnussen 1990;Koenig et al 1990) 0.5 30 min Specific airway resistance was increased significantly (Sheppard et al 1983) 0.6 2 days Bronchoconstriction (Linn et al 1984a) Nat Hazards (2007) 43:303-317 307 Koenig et al 1990). Exercising asthmatics, in particular, are already sensitive to pulmonary effects of SO 2 , when exposed to concentrations as low as 0.1 ppm and not more than 10 min exposure time (Sheppard et al 1981).…”
Section: Vulnerability Assessmentmentioning
confidence: 99%